Analisis Pengaruh Resonansi Merek dan Kepercayaan Merek terhadap Loyalitas Merek Pengguna Produk Handphone Xiaomi di Kabupaten Wonogiri - Andhika Luthfi Ramadestian; Sri Murwanti (Economic Reviews Journal, 2024)
The purpose of this study is to investigate how trust and brand resonance affect the brand loyalty of Xiaomi mobile phone product users in Wonogiri Regency. The target audience of this research is Wonogiri Regency residents who own Xiaomi smartphones. A total of 100 respondents who live in the Wonogiri Regency area and are more than 17 years old are the sample used. Using the Partial Least Square (PLS) 3.0 analysis methodology, the research data were analyzed quantitatively. Brand loyalty of Xiaomi smartphone users in Wonogiri Regency is proven to be positively and significantly influenced by the brand resonance variable, based on the findings. Xiaomi smartphone users in Wonogiri Regency show positive and considerable brand loyalty as a result of the brand trust variable. The findings of the f2 calculation show that brand resonance and brand loyalty are adequately correlated. Variations in the brand trust and resonance factors can explain shifts in the brand loyalty variable, according to the calculation of the R2 value.